Community informatics and the power of participation - Usha Sundar Harris (Asia Pacific Network, 2007)
This article discusses the potential of information and communication technology (ICT) for social capital and community empowerment in Pacific societies through case studies of internet use by online communities during various political crises in Fiji and emerging community media. It argues that despite being located on the fringe of the ICT boom, it is still possible for island communities to engage with media technology using participatory approaches to develop local content which is closer to their own realities and which reflects local cultures, values and individual aspirations.